2019
DOI: 10.2141/jpsa.0180118
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and Toxicity Studies of Lead and Mercury in Laying Hens: Effects on Laying Performance, Blood Metabolites, Egg Quality and Organ Parameters

Abstract: This study investigated bioaccumulation and toxicity derived from heavy metals in laying hens. The 160 52week old laying hens were divided into 5 treatments with 8 replicates of 4 birds per pen. The treatments consisted of the control diet (without heavy metals), control diet with half the available dosage (AD, 5 ppm lead and 0.2 ppm mercury), AD (10 ppm lead and 0.4 ppm mercury), 2-fold AD (20 ppm lead and 0.8 ppm mercury), and 3-fold AD (30 ppm lead and 1.2 ppm mercury), and were provided to the laying hens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The quantitative content of lead in the blood reflects the level of load on the body with its compounds, and the distribution of lead in the organs and tissues of animals depends on the intensity of blood circulation and affinity for metal (Kim et al, 2019;Wang et al, 2021). The results of our studies confirm that the determination of delta-aminolevulinic acid in the serum of poultry is necessary for the timely detection and correction of metabolic disorders caused by low doses of xenobiotics.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The quantitative content of lead in the blood reflects the level of load on the body with its compounds, and the distribution of lead in the organs and tissues of animals depends on the intensity of blood circulation and affinity for metal (Kim et al, 2019;Wang et al, 2021). The results of our studies confirm that the determination of delta-aminolevulinic acid in the serum of poultry is necessary for the timely detection and correction of metabolic disorders caused by low doses of xenobiotics.…”
Section: Discussionsupporting
confidence: 63%
“…Numerous current studies are devoted to the mechanisms of toxic effects of lead ions on animals and birds (Kim et al, 2019;Oladipo et al, 2020). The special danger of the ecotoxicant is explained by its ability to be accumulated in living organisms, to be included in a metabolic cycle, to form highly toxic organometallic compounds not being subjected to biological decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…However, some contrasting results were observed. Hg at 25–100 mg/kg as ethyl Hg chloride, and combination of Pb (30 mg/kg) and Hg (1.2 mg/kg) did not significantly depress egg quality of laying hens ( 16 , 28 ). Some previous studies have shown that organic or inorganic Cr had no effect or a slight increase in egg production ( 20 22 ).…”
Section: Discussionmentioning
confidence: 87%
“…Some reports have shown that the combined feeding of Pb and Cd leads to liver oxidative damage of laying hens ( 26 ) and decreased laying performance and egg quality ( 27 ). Kim et al ( 28 ) found that in-feed heavy metals for layer diets up to 30 mg Pb/kg and 1.2 mg Hg/kg decreased F 1 follicle weights simultaneously causing hepatic dysfunction as indicated by increasing blood metabolites that are associated with liver inflammation. Meanwhile, combined administration of methylmercury chloride (MeHgCl), lead acetate (PbAc), and cadmium chloride (CdCl 2 ) increased the severity of hepatic histopathologic changes and disturbed hepatic metal concentrations in Pekin ducks ( 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Pb is known as a ‘chemical time bomb' due to its toxicity which causes adverse effects on nervous and haemopoietic systems [ 10 ]. Children are particularly vulnerable to the neurotoxic effects of Pb exposure due to their developmental state, body weight and behaviours that increase the risk of exposure.…”
Section: Introductionmentioning
confidence: 99%